2016
DOI: 10.1159/000449413
|View full text |Cite|
|
Sign up to set email alerts
|

Tetrahydrocannabinol:Cannabidiol Oromucosal Spray for Multiple Sclerosis-Related Resistant Spasticity in Daily Practice

Abstract: Background: Tetrahydrocannabinol:cannabidiol (THC:CBD) oromucosal spray (Sativex®) is an add-on therapy for moderate-to-severe multiple sclerosis (MS)-related drug-resistant spasticity (MSS). Aim: The MOVE-2 EU study collected data from everyday clinical practice concerning the effectiveness and tolerability of THC:CBD. Methods: This was an observational, prospective, multicentre, non-interventional study. Patients with resistant MSS prescribed add-on THC:CBD oromucosal spray according to approved labelling, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 15 publications
4
40
1
Order By: Relevance
“…These studies demonstrated a meaningful reduction on physician‐judged relief of resistant spasticity in 75 per cent of patients after 1 month of treatment . There was improved spasticity scores and spasticity‐related symptoms at 3 months . The lack of a treatment comparison limits interpretation.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…These studies demonstrated a meaningful reduction on physician‐judged relief of resistant spasticity in 75 per cent of patients after 1 month of treatment . There was improved spasticity scores and spasticity‐related symptoms at 3 months . The lack of a treatment comparison limits interpretation.…”
Section: Resultsmentioning
confidence: 98%
“…Two large ( n =334 and n =433) multisite prospective observational studies were conducted using the same protocol . They examined the effects of nabiximols on spasticity in patients with multiple sclerosis .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations